Why are farmers reluctant to accept biological inputs? a structural equation model of technology adoption - Forouzani, Masoumeh; Bondori, Abolmohammed; Mombini, Ameneh Savari (Frontiers in Sustainable Food Systems, 2024)
Today, chemical inputs play an important and crucial role in increasing the production rate of agricultural products and the income of farmers in Iran. However, in parallel with this beneficial effect, the widespread and indiscriminate use of such inputs is considered to be one of the most significant barriers to environmental sustainability in Iran. The main objective of this research is to model the acceptance of the use of biological inputs among farmers living in the southwest of Iran. The research study was conducted using the cross-sectional survey method. The statistical population included all farmers of Meidavoud district located in Baghmalek county, southwest of Iran (N = 1,400). A sample of 302 individuals was selected according to Morgan’s sample size table and random sampling method. A questionnaire was used to collect the data, the validity of which was confirmed by a panel of experts, and its reliability was approved by various coefficients. The data were analyzed using SPSSV26, Smart PLS3, and AMOS software. The results of the structural equations showed that among the variables influencing farmers’ behavior toward biological inputs, the attitude and willingness variables could predict 80% of the variation in farmers’ behavior. In addition, attitude, ease of use, and usefulness were identified as effective factors in farmers’ willingness to use biological inputs. According to the results of the path analysis, the variables perceived usefulness and ease of use could predict 67% of the changes in farmers’ attitudes. To convince farmers and promote desirable attitudes that, in turn, influence their willingness to use biological inputs, some persuasive interventions seem to be necessary. Farmers need to be externally or internally motivated if they adopt environmentally friendly practices such as use of biological inputs.